Keberhasilan Pemungutan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Kabupaten Trenggalek - Bela Kusuma Wardani; Sri Dwi Estiningrum (Jurnal Akuntansi dan Pajak, 2022)
The Rural and Urban Land and Building Tax is a source of Regional Income that will later become a milestone for the development and progress of the region itself, therefore it is important to know how the effectiveness, growth rate and contribution of PBB-P2 collection for Regional Original Income is, these points also become the purpose of this research. The research method applied in this research is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The unit of analysis in this research is the Regional Finance Agency of Trenggalek Regency. The primary data source of the research is based on the results of interviews with the Head of Sub-Division of Data Collection, Registration, and Regional Tax Services and the Head of Sub-Division of Verification, Collection, Reporting, and Settlement of Regional Taxes, while the secondary data source comes from the Budget Realization Report of Trenggalek Regency for 2017-2021 The result of this study indicates that the effectiveness and growth rate of PBB-P2 in the Trenggalek Regency is quite effective, but it has a lesser contribution. Keywords : Collection, PAD, PBB-P2, Taxation.